2021
DOI: 10.1158/1055-9965.epi-20-1796
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Research of Rare Cancers: Trends, Resources, and Challenges

Abstract: Background: The goals of this project were to assess the status of NCI's rare cancer–focused population science research managed by the Division of Cancer Control and Population Sciences (DCCPS), to develop a framework for evaluation of rare cancer research activities, and to review available resources to study rare cancers. Methods: Cancer types with an overall age-adjusted incidence rate of less than 20 cases per 100,000 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Some of these cancers may contribute to even greater impairments in quality of life and therefore require increased attention in survivorship research. [29] For instance, our audit found that there were no abstracts that specifically addressed survivorship issues in people with rare cancers, such as liver malignancy or sarcoma. Although this highlights a gap in survivorship research for underrepresented cancers, [29,30] it may also be a reflection of existing infrastructure priorities and funding patterns.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some of these cancers may contribute to even greater impairments in quality of life and therefore require increased attention in survivorship research. [29] For instance, our audit found that there were no abstracts that specifically addressed survivorship issues in people with rare cancers, such as liver malignancy or sarcoma. Although this highlights a gap in survivorship research for underrepresented cancers, [29,30] it may also be a reflection of existing infrastructure priorities and funding patterns.…”
Section: Discussionmentioning
confidence: 98%
“…[29] For instance, our audit found that there were no abstracts that specifically addressed survivorship issues in people with rare cancers, such as liver malignancy or sarcoma. Although this highlights a gap in survivorship research for underrepresented cancers, [29,30] it may also be a reflection of existing infrastructure priorities and funding patterns. [28,31] Overall, the finding that most studies included mixed cancer types is encouraging considering that in many cases, cancer type is not always the primary determinant of how and whether survivors experience social and psychological issues, and interventions can be effective for a broad range of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, those malignancies are combined in the category “bone and joint” cancers. This, in addition to the fact that bone and joint cancers are understudied, is a practical concern that leaves patients, clinicians, and policy makers with limited information (Gallicchio et al, 2021 ; Greenlee et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the most common cancer sites were well represented by these recourses. Similarly, epidemiological studies and genomic resources were largely focused on common cancers, while rare cancers were studied to lesser extent (Gallicchio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 Given the limited studies on rare cancers, their occurrence increases, as a group of diseases that are characterized by significantly worse survival rates vs more common cancers. 9 These factors highlight the social need to get efforts on research into their biological basis, etiological factors, the most effective new therapies and the organization of healthcare to improve access to best practices and innovation. Complementarily, early diagnosis and diagnostic accuracy are among the first challenges to overcome, as approximately one-third of tumors are reclassified.…”
Section: ■ Introductionmentioning
confidence: 99%